Learning to understand: my life story to pakana philosophy - Keith Everett (2024)
WARNING: Aboriginal and Torres Strait Islander readers are warned that this thesis may contain references of deceased persons and content which may cause distress. I chose the title for this dissertation, ‘Learning to understand: My life story to pakana philosophy’, to reflect my story of learning what it means to be Aboriginal, my role in helping my community to gain rights as First Nations people, and my seeking another step in the Struggle: how to keep and maintain our connections with Country strong, now and into the future. This dissertation, first and foremost, tells my life story. Born in 1942 on Flinders Island, I grew up with my extended family who experienced racism and lack of opportunities. In 1947, my immediate family moved to Gippsland, country Victoria, and then to St Kilda, Melbourne, in 1953. My work on fishing boats took me back to Flinders Island when I was 16. I found my relatives again and saw fully for the first time that we were an Aboriginal community. My life from that time has been extraordinary. I have travelled across Australia and overseas as a soldier, fisherman, sailor, construction and demolition rigger, activist, public servant, community leader, writer, and student. In retelling my life story, I draw upon and explain my body of writing from the 1980s to the present: my poetry, short stories, essays, plays, films, and speeches. (A list of these works is included in my bibliography.) Chapters Three and Four link my life story and my writing to my encounters with contemporary Australian Aboriginal philosophy. I explain how I have been influenced by Aboriginal philosophers I have met: David Mowaljarlai, Uncle Max Dulumunmun Harrison, Bill Neidjie, Tyson Yunkaporta, Norm Sheehan, Victoria Grieves-Williams, and Laura Gower. While I use the word, ‘philosophy’ here, its meaning in English and the cultural West is conceptually different from my understanding of Aboriginal philosophy or Aboriginal Knowledge. Aboriginal philosophy exists outside of colonial structures: it is a ‘Oneness’ ...